Timeliness of Congenital Hypothyroidism Screening Services in the Work Area Period of January – March 2024 - Annisa, Fara (Rifa'Institute, 2024)
Introduction: Early detection and treatment of congenital hypothyroidism can reduce the risk of intellectual disability, so the timeliness of services is the key to the success of the congenital hypothyroidism (SHK) screening program in newborns. Objective: Evaluate the implementation of the SHK program for newborns in the work area of the Sampang Regency Health Office in January - March 2024. Method: Data on the timeliness of collection, specimen delivery to the laboratory and feedback data on screening results were collected through program records and reporting at health service facilities, the Sampang Regency Health Office, and the Dr. Soetomo Surabaya Clinical Pathology Laboratory. Result and Discussion: The timeliness of specimen collection in January was 484 (47.21%) specimens taken on time in February 298 (34.33%), March 436 (45%) of several babies who underwent SHK every month. The category of Too early (24-hour <) in January, February, and March was 221 (21.56%), 373 (42.97%), and 198 (20.43%) respectively. The timeliness of specimen delivery in January was 187 (18%) late specimens. The total number of unreadable specimens (reject) was 515 (18%) out of 2,862 SHK specimens sent to dr. Soetomo Laboratory. Conclusion: The timeliness of SHK sampling at the age of <24 hours (Too Early) was the highest in February, which was 373 (42.97%). The highest specimen delivery delay was in January 187 (18%). The most unreadable/uncheckable SHK papers (Reject) in March 193 (20%)